IT engagement as a blessing and a curse? Examining its antecedents and outcomes in organizations. (August 2020) - Pirkkalainen, Henri; Salo, Markus; Makkonen, Markus
Highlights: IT engagement entails excitement from IT use and increasing need to use IT. Organizational IT users experience IT engagement, which is not IT addiction. IT engagement is driven by normative pressures and information load. IT engagement leads both to increased strain and IT-enabled productivity. IT engagement helps IT users perform their job better. Abstract: Information technology (IT) engagement is defined as a need to spend more time using IT. Practice-based examples show that IT engagement can have adverse effects in organizations. Although users can potentially get more work done through IT engagement, observations show that the users might jeopardize their well-being and hamper their work performance. We aimed to investigate this complexity in the research on IT engagement by examining its potential antecedents and outcomes in organizations. Considering the potentially mixed outcomes, we developed a model to examine the effects of IT engagement on personal productivity and strain. We also aimed to explain the antecedents of IT engagement by drawing on the collective expectations for IT use. In particular, we examined the extent to which normative pressure on IT use drives users' information load and IT engagement. Finally, we sought to understand whether users' attempts to avert dependency on IT use reduced their IT engagement. Several hypotheses were developed and tested with survey data of 1091 organizational IT users. The findings help explain the role of normative pressure as a key driver of IT engagement and validate the positive and negative outcomes of IT engagement in organizations.